The Role of Cooperatives as a Source of Facilitators in the World of Agriculture (Review Article) - Fikriman Fikriman; Fuji Kacaya Mita; Setiono Setiono (Baselang, 2021)
The function of cooperatives is to develop the economic potential and capabilities of its members and society in general to improve economic and social welfare. Increasing the welfare of farmers is very important to pay attention to in order to improve the social life of farmers. This is inseparable from the role of cooperatives, cooperatives have an important role as providers of savings and loan capital, providers of agricultural production facilities, educators, and of course as facilitators with the aim of increasing the welfare of farmers. Cooperatives have the main role to be a tool for the guided economy, as the foundation of the economic life of the Indonesian nation, and the basis for regulating the people's economy. The purpose of this paper is to discuss the role of cooperatives as a source of facilitators in the agricultural sector for the welfare of the social life of farmers and supporting Indonesian agriculture.